#### Answer

$f^{-1}(x) = \sqrt[6] x, x\geq0$

#### Work Step by Step

$f(x) = x^{6} , x\geq0$
$y = x^{6}$
$x = \sqrt[6] y$
$f^{-1}(x) = \sqrt[6] x, x\geq0$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

$f^{-1}(x) = \sqrt[6] x, x\geq0$

$f(x) = x^{6} , x\geq0$
$y = x^{6}$
$x = \sqrt[6] y$
$f^{-1}(x) = \sqrt[6] x, x\geq0$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.